Evaluation of Talent Management Effectiveness in Upstream Oil and Gas Industry to Achieve Company Business Objective - Prawatiningsih, Gesit; Ghazali, Achmad (The Indonesian Journal of Business Administration, 2017)
Abstract - The current global situation and condition is impact the way business function and organization need to deal with this continuous change. People – intellectual capital and talent – are ever more critical to organizational strategic process. The efficiency in the management of resources must be carried out, expensive and scarce talented person who drives the company to be competitive, easy access to information and integration between countries would allow the search competition to find people. Talent is the fuel of human capital engine and in the organization refers to the core employees and leaders that drive the business forward. To gain competitive advantage and sustainability the demand for human capital drives talent management. Talent Management will help company do selection and identification and developing talent people to fill key position by succession planning to achieve organization business objective.Keyword : talent management, succession planning, employee development.